Visceral leishmaniasis relapse in Southern Sudan (1999-2007): a retrospective study of risk factors and trends. - Stanislaw Gorski; Simon M Collin; Koert Ritmeijer; Kees Keus; Francis Gatluak; Marius Mueller; Robert N Davidson (Public Library of Science (PLoS), 2010)
BACKGROUND: Risk factors associated with L. donovani visceral leishmaniasis (VL; kala azar) relapse are poorly characterized. METHODS: We investigated patient characteristics and drug regimens associated with VL relapse using data from Médecins Sans Frontières - Holland (MSF) treatment centres in Southern Sudan. We used MSF operational data to investigate trends in VL relapse and associated risk factors. RESULTS: We obtained data for 8,800 primary VL and 621 relapse VL patients treated between 1999 and 2007. Records of previous treatment for 166 VL relapse patients (26.7%) were compared with 7,924 primary VL patients who had no record of subsequent relapse. Primary VL patients who relapsed had larger spleens on admission (Hackett grade >or=3 vs 0, odds ratio (OR) for relapse = 3.62 (95% CI 1.08, 12.12)) and on discharge (Hackett grade >or=3 vs 0, OR = 5.50 (1.84, 16.49)). Age, sex, malnutrition, mobility, and complications of treatment were not associated with risk of relapse, nor was there any trend over time. Treatment with 17-day sodium stibogluconate/paromomycin (SSG/PM) combination therapy vs 30-day SSG monotherapy was associated with increased risk of relapse (OR = 2.08 (1.21, 3.58)) but reduced risk of death (OR = 0.27 (0.20, 0.37)), although these estimates are likely to be residually confounded. MSF operational data showed a crude upward trend in the proportion of VL relapse patients (annual percentage change (APC) = 11.4% (-3.4%, 28.5%)) and a downward trend in deaths (APC = -18.1% (-22.5%, -13.4%)). CONCLUSIONS: Splenomegaly and 17-day SSG/PM vs 30-day SSG were associated with increased risk of VL relapse. The crude upward trend in VL relapses in Southern Sudan may be attributable to improved access to treatment and reduced mortality due to SSG/PM combination therapy.